Can faith and freedom co-exist? When faith-based health providers and women's needs clash. Issue 1 (2nd January 2017) - O'Brien, Jon
ABSTRACT: Faith-based health providers are a major component of health services delivery in many developing countries, especially in sub-Saharan Africa. They receive millions of dollars annually from unilateral and bilateral aid agencies to deliver care. At the same time, they often use conservative interpretations of religious teachings to deny access to essential health care, including reproductive health care and HIV/AIDS prevention services. How can we balance the presence of faith-based providers against the rights and needs of women and other vulnerable populations to receive the care they need?